Molecular identification of python species: Development and validation of a novel assay for forensic investigations. (May 2015) - Ciavaglia, Sherryn A.; Tobe, Shanan S.; Donnellan, Stephen C.; Henry, Julianne M.; Linacre, Adrian M.T.
Highlights: A novel primer set to identify python species in forensic inquiries. Phylogenetic reconstruction accurately identifies species with statistical support. Primer pair shows high sensitivity, amplifying 30 fg or 9 mitochondrial DNA copies. The assay has demonstrated suitability to samples of poor quality. Validation tests demonstrate this assay as suitable for forensic investigations. Abstract: Python snake species are often encountered in illegal activities and the question of species identity can be pertinent to such criminal investigations. Morphological identification of species of pythons can be confounded by many issues and molecular examination by DNA analysis can provide an alternative and objective means of identification. Our paper reports on the development and validation of a PCR primer pair that amplifies a segment of the mitochondrial cytochrome b gene that has been suggested previously as a good candidate locus for differentiating python species. We used this DNA region to perform species identification of pythons, even when the template DNA was of poor quality, as might be the case with forensic evidentiary items. Validation tests are presented to demonstrate the characteristics of the assay. Tests involved the cross-species amplification of this marker in non-target species, minimum amount of DNA template required, effects of degradation on product amplification and a blind trial to simulate a casework scenario that provided 100% correct identity. Our results demonstrate that this assay performs reliably and robustly on pythons and can be applied directly to forensic investigations where the presence of a species of python is in question.